Implementation of by-laws with islamic approach in shaping the islamic way of life and culture by local authorities in Kelantan / Suzei Mat Nurudin, Zarina Mohd Zain dan Rasukhan Safiin - Nurudin, Suzei Mat; Zain, Zarina Mohd; Safiin, Rasukhan (UiTM Perak Press, 2022)
Local governments or known as local authorities are placed at the third tier after the federal and the state government administration. Local authorities are created and regulated under the Local Government Act 1976 and each has the power to enact suitable by-laws needed under their respective administration area. By-laws are defined as a formulation of the law under the jurisdiction of local authorities in performing its duties and functions covering the administrative area that has been identified by the state government. Since local authorities are the third tier, there are some controls imposed by the upper level of government in ensuring the effectiveness and efficiencies of services delivered. The by-laws were created to play an important part in affecting the daily lives of societies; especially in local authority areas which have quite different approaches such as Kota Bharu Municipal Council of Islamic Cities (MPKB-BRI) and other local authorities in Kelantan. This is because the by-laws implemented by the local authorities in Kelantan are very much different compared to local governments in other states in Malaysia as the by-law’s provisions are focusing on the Islamic approach that has been implemented. The implementation of the bylaws somehow does give some impact on the local communities and also the visitors to the state. The objectives of this study are to explore the implementation of the by-laws that focused on the Islamic approach implemented by the local government in Kelantan and gather feedback from the local communities on the impact especially in shaping their societal behaviour.